2017
DOI: 10.22581/muet1982.1704.30
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality Mapping using Geographic Information System: A Case Study of District Thatta, Sindh

Abstract: Access to safe and affordable drinking water for all is an important goal of SDGs (Sustainable Development Goals). Degradation of water quality of coastal aquifers is a major concern throughout the world including the Indus River delta. Looking at the present changing climate scenario, the study was conducted to assess and map the spatial variation in the groundwater quality of district Thatta using GIS (Geographic Information System). The groundwater samples from hundred (100) randomly selected hand pumps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…2b shows the spatial distribution of turbidity in groundwater in the study area. Higher turbidity levels in groundwater of some areas of the district are likely due to the use of poor quality strainer filter material in the suction line [22]. The high turbidity in the groundwater in the study area is similar to levels of turbidity found in the Southern districts of Sindh province of Pakistan by Memon et al [29].…”
Section: Analysis Based On Physicochemical Parameterssupporting
confidence: 76%
See 2 more Smart Citations
“…2b shows the spatial distribution of turbidity in groundwater in the study area. Higher turbidity levels in groundwater of some areas of the district are likely due to the use of poor quality strainer filter material in the suction line [22]. The high turbidity in the groundwater in the study area is similar to levels of turbidity found in the Southern districts of Sindh province of Pakistan by Memon et al [29].…”
Section: Analysis Based On Physicochemical Parameterssupporting
confidence: 76%
“…1a, b, c, respectively. In the area, the average annual rainfall is about 220 mm, while temperature ranges between 23.8-28.7°C [22,30]. In the area, the groundwater is the primary source of potable water, which is contaminated gradually due to seawater intrusion.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The excessive TDS effect on drinking water taste may lead to unwanted gastrointestinal irritation and physiological reaction. Previous studies in this area have also confirmed high EC and TDS [44][45][46], which raises serious concerns regarding the health of children in primary schools of Sindh province.…”
Section: Total Dissolved Solids (Tds)mentioning
confidence: 76%
“…Most of its area stretches in two district administrative boundaries of Sindh Province, Pakistan, i.e., Thatta, and Sujawal ( Figure 1). The area hardly receives about 220 mm of rainfall annually [14][15][16][17][18], mostly falls during monsoon periods. According to the 2017 Census, about 1.76 million people are living in these two districts.…”
Section: Study Areamentioning
confidence: 99%